Z adresownika poetki. Śladami listów Kazimiery Iłłakowiczówny w bibliotekach polskich - Chuda, Monika (My University, 2010)
Niniejszy artykuł porusza pomijane dotychczas w literaturze zagadnienie korespondencji wybitnej poetki i tłumaczki Kazimiery Iłłakowiczówny. Analiza charakteru spuścizny znajdującej się w czterech dużych bibliotekach: Bibliotece Kórnickiej PAN, Bibliotece Raczyńskich w Poznaniu, Wojewódzkiej i Miejskiej Bibliotece Publicznej w Bydgoszczy oraz Bibliotece Uniwersyteckiej w Poznaniu pozwala spojrzeć szerzej na problem niekompletnej i szczątkowej biografii poetki, równocześnie skupia tę rozproszoną dziś spuściznę. Bogata i różnorodna twórczość Kazimiery Iłłakowiczówny doczekała się wydania zbiorowego poezji (Toruń 1998) pod redakcją Jacka Biesiady i Aleksandry Żurawskiej--Włoszczyńskiej, inaczej jest z jej biografią. Zapomniany w historii literatury „słowik wileński” kryje się w swoich listach w archiwach zbiorów bibliotecznych. Bez Kazimiery Iłłakowiczówny barwna epoka międzywojenna wydaje się niekompletna. Traci mistrzynię osobliwej dyskrecji, metaforyzacji rzeczywistości oraz lekkiej ironii.

The present article discusses the correspondence of the distinguished poetess and translator, Kazimiera Iłłakowiczówna. In the literature of the subject these issues have not yet been addressed adequately and satisfactorily. An analysis of the nature of the written legacy of the poetess, currently housed in four large Polish libraries: Kórnik Library of the Polish Academy of Sciences, Raczyński Municipal Library in Poznań, Public Library in Bydgoszcz and Poznań University Library, allows us to have a broad outlook to issues related to the incomplete and fragmented biography of the poetess. At the same time, it makes it possible to integrate somehow this dispersed legacy. The rich and varied literary output of Kazimiera Iłłakiewiczówna has been finally integrated with the edition of a collection of her poems (Toruń, 1998, ed. Jacek Biesiada and Aleksandra Żurawska-Wołoszyńska. Unfortunately, this is not the case with Iłłakiewiczówna’s biography. The mysteries of the biographical past of the nearly forgotten “Wilno nightingale” still remain to be discovered in archives and library collections. Without Iłłakiewiczówna, the colourful epoch of the literary interwar period seems though to be incomplete. It clearly lacks the mistress of the singular discreetness, methaphorization of realities and her irony light as a breath.
From the addressbook and planner of a poetess. On the trail and through the letters written by Kazimiera Iłłakowiczówna currently held in Polish libraries
Keywords: Kazimiera Iłłakowiczówna; Spuścizna epistolograficzna; Epistolographical legacy; Korespondencja literacka; Literary correspondence; Poznań XX wiek; Poznań – 20th century